The EPA Conventional Reduced Risk Pesticide Program - Frederick M. Fishel (EDIS)
PI224, a 9-page fact sheet by F.M. Fishel, describes this program initiated by the Food Quality Protection Act of 1996 — advantages, criteria for consideration, carbamate and organophosphate pesticides, and current use trends. Includes additional sources of inforamtion and tables listing reduced risk and organophosphate alternative pesticides registered in the U.S. Published by the UF Department of Agronomy, January 2010.